On the mechanisms of dissolution of montroydite [HgO(s)]: Dependence of the dissolution rate on pH, temperature, and stirring rate - Hocsman, Ana (2006)
The dissolution behavior of montroydite (HgO) has been studied using a fully automated system. Dissolution data under equilibrium conditions are in agreement with previously published data and indicate that HgO solubility is relatively high and constant between pH 4 and 10.1 and increases markedly at pH < 4. The dissolution rate also has similar behavior: it is relatively high and constant between pH 4 and 10.1 and increases sharply at pH < 4. The dissolution process obeys a three-dimensional contraction or attrition mechanism. The dissolution rate increases with increasing temperature and stirring rate and is the result of mixed transport and reaction control. The rate of HgO dissolution is considerably higher than that of other divalent metal oxides at low pH. This high rate is due to the ability of Hg(II) to rapidly exchange its ligands. Data suggest that montroydite will only occur in nature in highly contaminated sites and indicate that Hg oxidation products that are formed at the liquid Hg/water interface may dissolve rapidly.